Diversidade al??lica em conjuntos de gr??os de p??len de Tabebuia Aurea baseada em marcadores microssat??lites - Trindade, Anne Karen Santos (2017)
The bees give a great contribution in maintaining genetic variability of plants from the Cerrado. Tabebuia aurea is a species of the family Bignoniaceae typical of the Cerrado, having large sized bees as its main pollinator. The dispersal of pollen by bees has been well-studied and genomic techniques can facilitate this type of study. This work aimed to develop strategies for the extraction and amplification of DNA from pollen grains of Tabebuia aurea. For this purpose, we collected pollen grains of bee legs caught in Parque Nacional de Bras??lia ??? DF, which subsequently underwent two different techniques of WGA (Whole Genome Amplification). The WGA amplification products were used to amplify 15 microsatellite loci, which were used for characterization of the genetic diversity of the pollen grains. The amplified fragments were separated by capillary electrophoresis in an automatic sequencer and the results were analyzed using the program Geneious. Twenty-two trees were evaluated and the characterization of the allelic diversity was held for groups of pollen grains, each containing 20 grains, from 31 bees; single pollen grains were also evaluated. The WGA technique OmnPlex was the one that produced the largest amount of genomic DNA allowing the amplification of different microsatellite loci. Using the DNA obtained by this technique as a template, all groups of pollen grains showed high rate of polymorphism with 10 or more alleles per locus. In addition, it was observed that most of the bees carry pollen from only one donor, indicating that bees remain for a long time in the same tree.